Reduced Intensity Conditioning Followed by Allogeneic Hematopoietic Stem Cell Transplantation Is a Good Choice for Acute Myeloid Leukemia and Myelodysplastic Syndrome: A Meta-Analysis of Randomized Controlled Trials - Song, Yanzhi; Yin, Zhichao; Ding, Jie; Wu, Tong (Frontiers in Oncology, 2021)
Background-Reduced intensity conditioning (RIC) before allogeneic hematopoietic stem cell transplantation (allo-HSCT) has been reported to have the same overall survival (OS) as myeloablative conditioning (MAC) for patients with acute myeloid leukemia (AML) in complete remission (CR) and myelodysplastic syndrome (MDS). However, results from different studies are conflicting. Therefore, we conducted a systematic review and meta-analysis guided by PRISMA 2009 to confirm the efficacy and safety of RIC vs. MAC for AML in CR and MDS. Methods-We search PubMed, Web of Science, Embase, Cochrane central, clinical trial registries and related websites, major conference proceedings, and field-related journals from Jan 1, 1980 to July 1, 2020 for studies comparing RIC with MAC before the first allo-HSCT in patients with AML in CR or MDS. Only randomized controlled trials (RCTs) were included. OS was the primary endpoint and generic inverse variance method was used to combine hazard ratio (HR) and 95% CI. Results-We retrieved 7770 records. Six RCTs with 1413 participants (711 in RIC, 702 in MAC) were included. RIC had the same OS (HR=0·95, 95% CI 0·64–1·4, P=0·80) and cumulative incidence of relapse as MAC (HR=1·18, 95% CI 0·88–1·59, P=0·28). Furthermore, RIC significantly reduced non-relapse mortality more than total body irradiation/busulfan based MAC (HR=0·53, 95% CI 0·36–0·80, P=0·002) and had similar long-term OS and graft failure as MAC. Conclusion- RIC conditioning regimens are recommended as an adequate option of preparative treatment before allo-HSCT for patients with AML in CR or MDS.